Pact4Skills Tackling the challenges of the European Education Area by building resilient, inclusive and forward-looking training to upskill HED students face the transformations in digital culture with new e-skills, intercultural and entrepreneurial competences - (:unkn) unknown (My University, 2024)
Digital technologies are omnipresent, whether in science, business, politics or even in the most private spheres. It was though the COVID-19 pandemic that accelerated the pace, making clear that the future will require the workforce to adapt and learn new skills in a fast-moving technological landscape, the cultural sector included. To remain competitive, the cultural domains need to apply the technology-intense-experience to innovate along with an entrepreneurial mindset besides recruiting and retaining talents. Research undertaken however by the Partnership in 2020 has revealed: 1.- CULTURAL CAPITAL DEFICIT: 2.- 4th INDUSTRIAL REVOLUTION 3.- SUPPLY- DEMAND DIVERGENGE 4.- VIOLENCE CONTAMINATION IN THE DIGITAL SPHERE